Thermal performance optimization of building floors under air-conditioning intermittent operation by numerical simulation. (September 2019) - Meng, Xi; Du, Junfei; Wang, Yating; Gao, Yanna
Under air-conditioning intermittent operation, there may be the large difference of air temperatures in two adjacent rooms due to different operation behavior, and thereby, interior envelops may cause great heat loss. Under this condition, floors may become the most vulnerable spot of the room heat preservation due to their large proportion in interior envelops and poor thermal insulation. To optimize the thermal performance of floors, three floor models were built to compare their thermal performance characteristics under air-conditioning intermittent operation, while a heat transfer model was built by the finite volume method and verified by experimental data. The results showed that an expanded polystyrene layer located close to the upper surface can improve the thermal performance of the bottom floor, while the continuous integration of an air space ceiling placed close to the lower surface can improve the thermal performance of the top floor obviously. The daily cooling load formed by the cast-in-place-reinforced concrete floor integrated with the expanded polystyrene layer and the air space ceiling can reduce the daily cooling load by 53.27% and 47.00%, compared with the cast-in-place-reinforced concrete floor and the cast-in-place-reinforced concrete floor only integrated with the expanded polystyrene layer.